The mental capacity and its relation its relation to the performance of skills and transmitter reception of volleyballfor female students - م .م ساهره محمد عبد الأمير أ . د انتصار عويد أ . د لمى سمير (الرياضة المعاصرة)
The importance of the study is the interest of educational institutions in obtaining the best learning as well as the role of mental capacity in acquiring mental skills and all scientific activities, and how mental capacity is the most important factor affecting how to deal with knowledge and information and activities, whether sports or otherwise.    The problem of research is increase in information, which may lead to exhaustion of mental capacity, which may cause poor performance of the basic skills of volleyball, and this is what we aspire to. The study also addressed a study aimed at identifying the mental capacity values ​​of the students in the preparatory school.    And also to identify the values ​​of the performance of the skills of preparation and reception of volleyball and knowledge of the role of mental capacity in the performance of the skills under study here